Structural assessment of family and educational influences on student health behaviours: Insights from a public health perspective - Zhuo Su; Daifeng Yang; Chun Wang; Zhenlin Xiao; Shanshan Cai (PLoS ONE, 2025)
The 2024 World Health Organization report reveals that 81% of adolescents worldwide fail to meet the recommended level of physical activity, highlighting a serious global public health challenge. This study approaches the issue from a public health perspective by focusing on the structural determinants of health behavior among university students. Although student health behaviors are shaped by both individual and structural factors, existing research has predominantly emphasized individual-level influences, overlooking the broader educational and systemic context. Employing a structural analysis framework, this study mapped the causal and hierarchical relationships among factors influencing student health behaviors. Data were collected through structured questionnaires administered to undergraduate and postgraduate students in Hunan Province, China. The model identifies family support as the foundational layer in the hierarchy, exerting significant influence on psychological well-being and health motivation, which in turn regulate physical activity and dietary choices. The findings underscore the critical mediating role of educational environments in amplifying the effects of family structures. Based on these insights, this study advocates for the integration of family resources into school-based health promotion interventions, such as digital platforms for parent–student communication, joint family–university health workshops, and collaborative educational health campaigns. Embedding family-oriented strategies into formal education systems may enable universities to enhance student physical and mental well-being in a more integrated and sustainable manner within a public health framework.